"How do you like them now?" Expected reactions upon discovering that a friend is a political out-group member. (October 2020) - Buliga, Elena; MacInnis, Cara
Republican or Democrat participants imagined how they would respond upon learning about the political group membership of a potential or established friend. Four vignettes (friend political in-group; friend political out-group; potential friend political in-group; potential friend political out-group) were presented in a random order. After each, participants provided expected reactions. Overall, reactions (e.g., hope of the relationship lasting, intentions to engage in friendship maintenance behaviors, trust) were most positive toward the established in-group friend, followed by potential in-group friend, then the established out-group friend, and lastly the potential out-group friend. That is, participants expected to be more positive toward a person they just met than an established close friend, simply due to knowing these individuals' political group memberships. Some of these differences were moderated by intergroup attitudes or political identification. Discoveries of political group membership may influence the development or maintenance of friendships.